Genome-wide characterization and expression analysis of WRKY family genes in the biosynthesis of triptolide in Tripterygium wilfordii - Limei Tang; Xinyu Qi; Jiayu Chen; Yujun Zhao; Junhao Gu; Shanshan Zhu; Wei Gao; Lichan Tu (BMC Genomics)
Abstract Background WRKY transcription factors play a vital role in regulating plant growth, development, and secondary metabolism. Tripterygium wilfordii is a medicinal plant that has been widely utilized in rheumatoid arthritis therapy; it contains triptolide, a prominent bioactive constituent exhibiting potent anti-inflammatory and anti-tumor properties. However, the mechanism underlying the regulatory effects of WRKY on triptolide biosynthesis is poorly understood. Results In this study, 95 TwWRKY genes were identified in the T. wilfordii genome, which were divided into three groups. Phylogenetic analysis indicated that the TwWRKY were conservative relative to other plants. Collinearity analysis revealed that gene duplications played a crucial role in the evolution of this gene family. Transcriptome data from various plant tissues were integrated by correlation analysis, and a gene-to-metabolite network was successfully mapped; consequently, 32 TwWRKY genes were selected as potential regulators of triptolide biosynthesis. Furthermore, the expression changes in the 32 TwWRKY genes were analyzed following methyl jasmonate (MeJA) induction, and the key candidates likely to regulate the biosynthesis of triptolide were screened. Finally, we performed subcellular localization on the key candidate gene TW23G00056.1 and found that it plays its biological role in the nucleus. Conclusion Our study provides a valuable resource for further research on TwWRKY in T. wilfordii. The candidate genes reported here lay the foundation for elucidating the regulatory mechanism of triptolide.